Media Development Study Basic Techniques Of Handball Ball Based Adobe Flash Player On Coaching Extracurricular Son Handball Junior High School Level In Demak District - Sadullah, Akhmad; Kristiyanto, Agus; Purnama, Sapta Kunta (JTIKOR (Jurnal Terapan Ilmu Keolahragaan), 2019)
AbstractThe background of this research is the unavailability of learning model of basic technique of hand ball which is used as a reference to build the ability of basic technique of hand ball among the students. The purpose of this research is to develop the basic technique of handball based technique of handball based on adobe flash player, including opening, passing, catch the ball, dribble, blocking, shoot the ball, goalkeeper training and stretching, all of which are arranged in one easily accessible media anytime, by anyone and anywhere, especially at the Se-degree Junior High School in Demak district. The research method used is "Reasearch and Developement" approach. "This research is a research and development through preliminary stage, development of learning design, production, and product evaluation. After the production phase, then the initial product validation stage by media experts, academicians and practitioners. The evaluation results of media experts for the assessment component containing aspects of text, images / photos, sound audio, video obtained 61% of the total for the feasibility conclusion of the product. The results of the evaluation of academicians for the assessment component containing aspects of conformity, usefulness, security, and aspects of implementation are 85.71% of the total for the feasibility conclusion of the product. The results of the expert evaluation of practitioners for the assessment component containing aspects of conformity, usefulness, security, and the implementation aspect obtained 97.86% of the total for the feasibility conclusion of the product. The final percentage of all experts is 81.58% and it can be interpreted that the design of Adobe Flash Player based hand baseball technique technique can be tested in the next step. Small group test results for the assessment component that contains aspects of conformity, usefulness, security, and aspects of implementation obtained 71.25% of the overall for the feasibility of the conclusion of the product. The results of the large group test for the assessment component that contains aspects of conformity, usefulness, security, and the implementation aspect obtained 87.92% of the overall for the feasibility conclusion of the product. Based on the specified criteria it can be concluded that Adobe Flash Player's handmade basic ballast technique technique products are valid and usable. This is because the data results are stretched 80 - 100% for clarification of product feasibility percentage. Therefore this product is feasible and effective to develop the extracurricular handmade coaching in Demak Regency. Keywords: Multimedia Learning, handball, adobe flash player